The early settlement of HD-5 at Raʾs al-Ḥadd, Sultanate of Oman (fourth-third millennium BCE) - Borgi, Federico; Maini, Elena; Cattani, Maurizio; Tosi, Maurizio (Proceedings of the Seminar for Arabian Studies, 2012)
The site of HD-5 is a well-preserved archaeological mound located on a rocky outcrop facing the ocean waters of the Arabian Sea at Raʾs al-Ḥadd in the easternmost corner of the Sultanate of Oman, just 3 km south of the actual headland. First recorded by the Joint Hadd Project in 1987, the site was mapped and numbered by the British Museum Expedition a year later and briefly explored in 1988 with limited test trenches. This paper presents the result of more systematic excavations carried out by the Joint Hadd Project between December 2010 and January 2011. The latest occupation, dated to the second half of the third millennium BCE for the presence of Harappan wares, is formed by a thick dark ashy layer with several overlapping fireplaces. According to the present data, the early phase covers the entire fourth millennium BCE. The deposit is characterized by a series of post-holes indicating sub-oval huts or shelters.